(untitled) (The Review of Diabetic Studies, 2022)
BACKGROUND: Chronic limb ischemia (CLI) is strongly associated with increased mortality in diabetes patients. OBJECTIVE: The aim of this study was to evaluate factors affecting mortality within 1 year after endovascular revascularization in CLI patients. METHODS: This retrospective cohort study was based on medical records from the Integrated Cardiovascular Centre of Dr. Cipto Mangunkusumo National General Hospital, a tertiary care hospital in Jakarta, Indonesia. The study included 199 CLI patients with type 2 diabetes mellitus (T2DM) who underwent endovascular revascularization from January 2008 to June 2018. The patients were followed up for 1 year after endovascular revascularization. Kaplan-Meier and Cox proportional hazard analysis was used to analyze the data. RESULTS: 1-year survival probability was 58.8%. Cox proportional hazard analysis showed that duration of diabetes (HR 3.52; 95% CI 1.34-9.22), anemia (HR 2.59; 95% CI 1.47-4.56), and smoking (HR 2.49; 95% CI 1.46-4.27) were significantly associated with mortality within 1 year after endovascular revascularization. CONCLUSIONS: In T2DM patients with CLI, duration of diabetes, anemia and smoking were associated with a higher risk of mortality within 1 year post endovascular revascularization